CGIAR Genebank Platform - Plan of Work and Budget 2020 - CGIAR Genebank Platform (CGIAR Genebank Platform, 2020)
As per previous years, the CGIAR Genebank Platform is responsible for providing healthy, viable, documented germplasm from the 35 crop and tree collections managed by the CGIAR, which are maintained and safety duplicated in long-term conservation in accordance with the FAO Genebank Standards (2014) and Article 15 of the International Treaty on Plant Genetic Resources for Food and Agriculture (Plant Treaty). This service remains the most important annual output of the 11 CGIAR genebanks, which together are expected to distribute approximately 100,000 samples of germplasm in response to requests from up to 2000 external users and CGIAR scientists in 2020.